On the Use of Special Functions for Analyzing the Steady State Creep in Short Fiber Composites Semi-theoretically - Vahid Monfared; Saeed Daneshmand (Materials Research, 2015)
In this paper, a novel method is presented to obtain some unknowns such as displacement rate using special and well-behaved functions for short fiber composites in the steady state creep by semi-theoretical method (STM). The creep behaviors are predicted in the short fiber composites under tensile axial stress. Also, the regions under the partial debonding are predicted by the obtained results along with the reason of the partial debonding. The main purpose of this research is the use of the mathematical model instead of the time consuming and expensive experimental methods. On the other hand, the creep unknowns are simply obtained by the special functions rather than some complex theories. The use of sensor is one of the important applications of the present method in the regions with uniform behaviors. The obtained analytical results are validated by FEM results. Average difference between the analytical method and FEM results is about 10% approximately. Finally, good agreements are found between the obtained analytical and FEM results for predicting the creep behavior.